Menentukan Variabel Desain Iklan Menggunakan Voice of Customer - ribangun bamban Jakaria; Wiwik Sumarmi; Iswanto (2477 - 6165, 2022)
The corporate world is undergoing a very rapid rate of change. It's no wonder that manufacturers are competing to sell their products quickly in the market. Advertising is a medium that is used as a means to distribute information to the public, related to the product you want to be known, one of which is advertising that is used on television. By paying attention to this, when designing an advertisement, the thing that must be considered is the attributes attached to the advertisement, in order to provide interest to consumers or potential consumers. The purpose of this study was to determine the dominant product attributes on consumer interest in making decisions to continue viewing service advertisements on advertising impressions in digital media. The final result to be achieved is that the product design of advertisements is made able to improve product performance, provide convenience for business actors in determining ergonomic designs on digital media and optimize the performance of marketing tools in introducing products so that product designers are able to provide guarantees for the design of advertisements displayed. Become the preferred ad. This study uses customer voice analysis in the Quality Function Deployment (QFD) method by testing some initial attributes which show the results that some attributes have a significant influence on the design of advertising products.